2015
DOI: 10.1016/j.ajpath.2015.01.029
|View full text |Cite
|
Sign up to set email alerts
|

Type III Collagen Directs Stromal Organization and Limits Metastasis in a Murine Model of Breast Cancer

Abstract: Breast cancer metastasis is the leading cause of cancer-related deaths in women worldwide. Collagen in the tumor microenvironment plays a crucial role in regulating tumor progression. We have shown that type III collagen (Col3), a component of tumor stroma, regulates myofibroblast differentiation and scar formation after cutaneous injury. During the course of these wound-healing studies, we noted that tumors developed at a higher frequency in Col3(+/-) mice compared to wild-type littermate controls. We, theref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
90
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(98 citation statements)
references
References 72 publications
4
90
0
4
Order By: Relevance
“…Parity appears to increase collagen I deposition, but in an unorganized, uncrosslinked form, resulting in softer ECM and reduced risk of breast cancers [83]. Collagen III disrupts formation of dense, organized collagen I networks, resulting in softer ECM [94]. Loss of collagen III in mouse models is associated with tumor aggressiveness [94], though Col III is often observed to be overexpressed with increasing tumor grade [20,81,82,95].…”
Section: Microstructure Biomechanics and Crosslinkingmentioning
confidence: 99%
See 1 more Smart Citation
“…Parity appears to increase collagen I deposition, but in an unorganized, uncrosslinked form, resulting in softer ECM and reduced risk of breast cancers [83]. Collagen III disrupts formation of dense, organized collagen I networks, resulting in softer ECM [94]. Loss of collagen III in mouse models is associated with tumor aggressiveness [94], though Col III is often observed to be overexpressed with increasing tumor grade [20,81,82,95].…”
Section: Microstructure Biomechanics and Crosslinkingmentioning
confidence: 99%
“…Collagen III disrupts formation of dense, organized collagen I networks, resulting in softer ECM [94]. Loss of collagen III in mouse models is associated with tumor aggressiveness [94], though Col III is often observed to be overexpressed with increasing tumor grade [20,81,82,95]. Furthermore, reductions in collagen I density via TGFβ blockade likewise suggest that altering collagen network structure is a potential therapeutic target [96].…”
Section: Microstructure Biomechanics and Crosslinkingmentioning
confidence: 99%
“…For example, established histology dyes (Masson's trichrome, Movat's pentachrome, picrosirius red [PSR]), [15][16][17][18] antibody detection, 19 polarization-based widefield imaging, 20 and second harmonic generation (SHG) imaging 21,22 have all been employed. Other imaging methods often associated with collagen imaging either do not offer the appropriate resolution for the assessment of collagen organization, such as optical coherence tomography, 23,24 or require non-routine sample preparation methods and offer limited field of view, such as transmission electron microscopy, 25 scanning electron microscopy, 26 and atomic force microscopy.…”
Section: Research-article2016mentioning
confidence: 99%
“…Recent evidence has shown that the tumour microenvironment plays a crucial role in regulating tumour progression by different mechanisms, such as suppression of the immune response and remodelling of the extracellular matrix (ECM). 2 In particular, the remodelling of collagen fibres at the tumour-stromal interface has been shown to adversely affect survival. 3 Stromal regions can be characterised according to their maturity.…”
Section: Introductionmentioning
confidence: 99%